2002
DOI: 10.2224/sbp.2002.30.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Parental Child Rearing and Suicidal Ideation in Chinese Adolescents

Abstract: Three hundred and sixty-five Chinese adolescent boys and girls participated in a study of the relationship between perceived maternal and paternal warmth and control in child rearing, and suicidal ideation. Results of correlation and stepwise multiple regression analyses of data generated by the Parental Acceptance-Rejection Questionnaire, the Autonomy-Control Scale, and the Scale for Suicide Ideation showed that Chinese adolescents who experienced their mothers as less warm and affectionate tended to suffer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 10 publications
3
12
0
Order By: Relevance
“…The finding that conflict and harmony factor has a stronger relationship with adolescent suicidal ideation is in line with overseas and local findings [14,38]. Traditionally, Chinese people emphasized avoidance of interpersonal conflict and cultivation of interpersonal harmony, as revealed in the Chinese cultural sayings of "jia he wan shi xing" (if a family lives in harmony, everything will prosper) and "jia shaui kou bu ting" (a family will wither if there are many quarrels).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The finding that conflict and harmony factor has a stronger relationship with adolescent suicidal ideation is in line with overseas and local findings [14,38]. Traditionally, Chinese people emphasized avoidance of interpersonal conflict and cultivation of interpersonal harmony, as revealed in the Chinese cultural sayings of "jia he wan shi xing" (if a family lives in harmony, everything will prosper) and "jia shaui kou bu ting" (a family will wither if there are many quarrels).…”
Section: Discussionsupporting
confidence: 73%
“…There are studies showing that adolescent suicidal ideation was related to family dysfunction, family discord, poor family environment, family rigidity, family conflicts and poor adaptability [11,12]. Studies also showed that low levels of family cohesion and support as well as high levels of parent-adolescent conflict were positively related to depression and suicidal ideation [13,14]. However, a study by Mitchell and Rosenthal [15] yielded inconsistent results.…”
mentioning
confidence: 99%
“…Overall, the findings of the present study were consistent with those of previous studies (e.g., Chen, 1994;Chung et al, 1987;Fong, 1993;Lai & McBride-Chang, 2001;Lau, 1994;Wong et al, 2002) which found that in Hong Kong perceptions of negative parental practices are associated with adolescent suicidal ideation, as is the case in Western countries.…”
Section: Discussionsupporting
confidence: 92%
“…There were three hypotheses. Two were based solely on findings of Western studies, but it was felt that they had cross-cultural validity because the connection between perceptions of parenting styles and adolescent suicidal ideation in Hong Kong is quite similar to that of the West (Chen, 1994;Chung, Luk, & Mak, 1987;Fong, 1993;Lai & McBride-Chang, 2001;Lau, 1994;Wong, De Man, & Leung, 2002). The first hypothesis was that if being the favored child leads to a successful development (Adler, 1932;Freud, 1970) whereas being the nonfavored child leads to negative outcomes, then there should be a linear relationship between favoritism and suicidal ideation, with nonfavored adolescents reporting greater suicidal thinking.…”
mentioning
confidence: 99%
“…There are studies in Hong Kong and the U.S. showing that family processes are related to adolescent suicidal ideation. In Hong Kong, different studies revealed that an uncaring family environment, negative family climate, low levels of family cohesion and support, high level of parent-adolescent conflict, parental rejection, and too much control were associated with adolescent suicidal thoughts [5,9,10]. Similarly, previous studies in the U.S. found that adolescent suicidal ideation was positively related to family dysfunction, family discord, poor family environment, family rigidity, family conflicts, and poor adaptability, but negatively related to perceived parental support and family support [11,12,13].…”
Section: Suicide Statistics and Related Phenomena In Hong Kong And Thmentioning
confidence: 99%